Sources of primary school teachers’ self-efficacy in dealing with bullying among students: A case study in rural primary school teachers in Sarawak. - Lee, J.C.; Abdul Rahman, N.A.; Mohan, R. (JESS, 2017)
Whenever a teacher deals with bullying it is also very important for students to have teacher whom they see as taking an active stand against bullying in terms of propagating anti bullying norms and having an efficacious approach to decreasing bullying. But there is also evidence suggesting that teachers might be less effective in dealing with bullying among students in schools. On the other hand, it is not fair to judge or perceive a teacher as less effective or less efficacious when comes to dealing with bullying because the development of teachers’ self-efficacy in this matter could be influenced by some variables that serve as sources of efficacy among teachers. As the one who actually engaged in dealing with this destructive behavior, little attention was paid to sources of influence of teachers self-efficacy in dealing with bullying among students in primary school setting. This quantitative research utilizes a correlation method in order to examine the relationship between various sources of influence and teacher sense of efficacy when dealing with bullying among students in rural primary schools. Based on the standardized regression coefficients (βs) indices of direct effects of each predictor variable on each sub scale of teacher selfefficacy in dealing with bullying among students, Verbal Persuasion and Physiological Arousal had significantly predicted Behavioral Self-efficacy, Cognitive Self-efficacy and Emotional Self-efficacy in dealing with bullying among students in primary school. Based on the finding of this study, verbal persuasion and physiological arousal are prominent predictors of teacher selfefficacy in dealing with bullying among students in rural primary schools. It is recommended that teacher preparation or teacher developmental programs regarding the issue of bullying among students in rural primary schools, explicitly address these two influences with specific types of training and educational experiences that focus on mastery building through cognitive and meta cognitive strategies, cultivating self-regulation competencies, and establishing a social support system.